Ultrastructure of endometrial surface relief in normal menstrual cycle and after hormonal stimulation - Novotný, Radko; Malínský, Jiří; Oborná, Ivana; Dostál, Jiří (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1999)
Ultrastructure of the superficial relief of the endometrial epithelium was investigated under the scanning (SEM) and transmission electron microscopes (TEM) in a group of patients after the hormonal stimulation, performed in the program of in vitro fertilization and embryotransfer. The results were compared with those obtained in a group of patients studied during the secretory phase of normal menstrual cycle. Total 26 bioptic samples were subjected to the investigation, 13 in each group. Different types of the epithelial surface were classified in TEM and SEM and their relative amount was evaluated quantitatively in TEM. Special attention was paid to the pinopodes, considered as specific markers of the nidation window. Differences in the number of pinopodes were observed under the SEM in two groups of patients after different schemes of the hormonal treatment. These differences were not manifested under the TEM due to the small frequency of pinopodes in the ultrathin sections. The ultrastructural changes observed in the two groups of patients after different schemes of hormonal stimulation can be considered as signs of the changed metabolic activity of the endometrial epithelium and they can reflect the different endometrial receptivity for nidation.
Keywords: Female; Clomiphene; Microscopy, Electron; Follicle Stimulating Hormone; ženské pohlaví; folikuly stimulující hormon; Menstrual Cycle; Microscopy, Electron, Scanning; menotropiny; endometrium; lidé; mikroskopie elektronová rastrovací; Epithelial Cells; elektronová mikroskopie; menstruační cyklus; Menotropins; choriogonadotropin; Chorionic Gonadotropin; Endometrium; buněčná membrána; epitelové buňky; klomifen; Cell Membrane; Humans